PENGARUH GOOD CORPORATE GOVERNANCE DAN RISIKO BISNIS (BUSINESS RISK) TERHADAP KINERJA KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2017 SAMPAI 2019) - Anisa Rahmadani; Makhdalena Makhdalena; RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This study aims to examine the effect of independent board of commissioners, audit committee, board of commissioners, board of directors and business risk on financial performance either simultaneously or partially in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017 to 2019 The population of this study are all food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2017 to 2019, which have data on ROA, Independent Board of Commissioners, Audit Committee, Board of Commissioners, Board of Directors and Business Risk, totaling 14 companies. This study uses secondary data sourced from   existing records at the company and from other sources such as conducting a literature study with books related to the object of research or using data from the Central Bureau of Statistics (BPS). The data analysis technique used is path analysis with the help of the SPSS (Statistical Package for Social Science) program. The results of the study indicate that the results of the study indicate that the independent board of commissioners, audit committee, board of commissioners, board of directors and business risk simultaneously affect financial performance. The independent board of commissioners partially has a negative effect on financial performance. The audit committee has a positive effect on financial performance. The board of commissioners has a positive effect on financial performance. The board of directors has a positive effect on financial performance. And business risk has a negative effect on financial performance.Key Words : Independent Board of Commissioners, Audit Committee, Board of Commissioners, Board of Directors, Business Risk, Financial Performance